2021
DOI: 10.1017/s1355617720001332
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Fatigue and Processing Speed in Children Treated for Brain Tumours

Abstract: Objective: The relationship between fatigue and cognition has not been fully elucidated in children and adolescent survivors of brain tumours. The aim of the present study was to investigate the potential relationship between fatigue and cognitive impairments in these survivors, as this group is at risk for both types of deficits. Methods: Survivors of paediatric brain tumours (n = 45) underwent a neuropsychological testing on average 4 years after diagnosis. Mean age at follow-up was 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
(134 reference statements)
2
5
0
Order By: Relevance
“…One study has also shown associations between cognitive fatigue and processing speed in pediatric brain tumor survivors. 28 Our study demonstrates that the comprehensive neuropsychologic assessment and the neurological reports revealed more and diverse problems than could be inferred from the IQ measurements alone.…”
Section: Potential Risk Factors Before Rtmentioning
confidence: 68%
“…One study has also shown associations between cognitive fatigue and processing speed in pediatric brain tumor survivors. 28 Our study demonstrates that the comprehensive neuropsychologic assessment and the neurological reports revealed more and diverse problems than could be inferred from the IQ measurements alone.…”
Section: Potential Risk Factors Before Rtmentioning
confidence: 68%
“…We expected to find an association between children who received radiotherapy and fatigue since radiotherapy is a known risk factor for decreased processing speed and cognitive decline, 6 which has been associated with more cognitive fatigue in PBTS. 30 The reasons we did not find such an association could be that, first, the number of children in this cohort who had radiation was too small ( n = 37, 33%). Second, the large heterogeneity in our cohort makes it difficult to detect such a possible effect in univariable analyses, and we had insufficient power to explore this in multivariable analyses.…”
Section: Discussionmentioning
confidence: 80%
“…A score more than 1.5 standard deviations (SD) below the norm mean for the corresponding age group was considered to be an indicator of fatigue. The cut-off of − 1.5 SD was based on previous research on cancer-related fatigue [ 6 , 17 , 18 ]. The dichotomous results from assessment T3 were used as outcome variables, with the course of fatigue during treatment, sex, risk group, serious adverse event, and age at diagnosis as independent variables.…”
Section: Methodsmentioning
confidence: 99%